Research on the impact of digital transformation on the high-quality development of enterprises - Meng, Rui (Transactions on Social Science, Education and Humanities Research, 2024)
In recent years, under the background of mass entrepreneurship and innovation, China has vigorously promoted the digital transformation of enterprises. Taking A-share listed companies in Shanghai and Shenzhen Stock exchanges from 2012 to 2022 as samples, this paper empirically tests the relationship between corporate digital transformation and high-quality development of enterprises. At the same time, the internal control of enterprises and the degree of financing constraints play a regulatory role between digital transformation and high-quality development of enterprises; In the samples with different ownership nature and whether they are high-tech enterprises, the effect of enterprise digital transformation on the high-quality development of enterprises is different.